CONTROVERSIAL LAW ISSUES IN THE ENFORCEMENT OF THE NEW LEGAL PROVISIONS IN FAMILY LAW - Dan LUPAȘCU (Challenges of the Knowledge Society)
The relatively short period of the new Romainian Civil Code implementation highlights the existence of some controversial law issues regarding the legal provisions contained in Book II, entitled “About family”. Apart from the theoretical disputes, there are also court decisions that contain different solutions in the enforcement of the same legal provisions. Controversy exists not only in relation to the newly introduced institutions in our legal landscape, but also regarding the ones taken over from the old regulation, institutions that have undergone some changes. The examples are most varied and they do not bypass almost any matter. Thus, we signal the presence of different interpretations of regulations regarding: engagement, marriage, divorce, parentage, adoption, the legal duty to maintain, the parental authority, etc. The present study highlights such controversy’s by presenting the views expressed and the arguments invoked in their support and also some propositions of Ferenda Law.